Differences in antioxidant activity of guyabano leaf tea from cold and hot steeping methods - Desierdo, Bryan Kenneth V.; Dumelod, Benelyn D. (Quezon City University of the Philippines Diliman, 2024)
This study focused on the determination of the differences in antioxidant activity of guyabano leaf tea prepared from powdered guyabano leaves using the cold and the hot steeping methods. In the preliminary study, consumer panelists evaluated the sensory attributes of the guyabano leaf tea with medium-chain triglyceride (MCT) oil and found that it was generally not accepted, with mean acceptability score of 5.5 only. The mean Total Phenolic Content (TPC) of the hot-steeped guyabano leaf tea is 8.4 x 105 µg gallic acid equivalents (GAE)/g powder (or 6.7 x 105 µg gallic acid equivalents (GAE)/100 mL guyabano leaf tea) which is significantly higher (p < 0.05) than that of cold steeping with a mean of 5.4x 105 µg GAE/g powder (or 4.3 x 105 µg gallic acid equivalents (GAE)/100 mL guyabano leaf tea). The antioxidant activity of the guyabano leaf tea in terms of 2,2-diphenyl-1-picrylhydrazyl (DPPH) half-maximal inhibition (IC50), DPPH inhibition (%), and ferric reducing antioxidant power (FRAP), was predicted using linear models. TPC positively related with the antioxidant power of the tea, validating the hypothesis that increased TPC means increased antioxidant power of tea. Predicted antioxidant activity in terms of DPPH half-maximal inhibition (IC50) of guyabano leaf tea in this study are 115.43 µg/mL for hot-steeped and 120.26 µg/mL cold-steeped tea, lower than the reported value in literature (291.11 µg/mL). Predicted FRAP of both teas were negative, -374.3218 mmol Fe2+/g for hot-steeped and -910.7506 mmol Fe2+/g for cold-steeped tea, using extrapolation. Predicted DPPH inhibition (%) are 64961% for hot-steeped and 41864% for cold-steeped guyabano leaf tea, using extrapolation. Over- and underestimation of values may suggest the need to explore nonlinear regression.
In partial fulfillment for the Degree of Bachelor of Science in Food Technology
Thesis
Keywords: Sensory evaluation; Food -- Sensory analysis; Linear regression analysis; Powdered guyabano leaf tea; Hot and cold-steeping.